2019
DOI: 10.1016/j.jagp.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Psychosocial Interventions for Depression and Anxiety in Patients With Age-Related Macular Degeneration: A Systematic Review

Abstract: Purpose: To review the current literature on psychosocial and psychological interventions to prevent and treat depression and anxiety in patients with age-related macular degeneration (AMD). Methods: We conducted a systematic review of literature evaluating psychosocial and psychological interventions for depression and anxiety in AMD patients. Primary searches of PubMed, Cochrane library, EMBASE, Global Health, Web of Science, EBSCO, and Science Direct were conducted to include all papers published until Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 81 publications
0
17
0
1
Order By: Relevance
“… 160 Outcomes of these interventions may also depend largely on the age of the individual. While prior studies of psychosocial interventions demonstrate some degree of efficacy in older adults with vision loss, and particularly AMD, 161 meta-analytic findings indicate that improvements are less robust in elderly samples. 160 Related to this finding, risk and protective factors for mental health problems in older adults may be different from those of younger people, 29 and therefore treatment may need to be adapted to fit the individual needs of the consumer.…”
Section: Part Ii: Mental Health Assessment and Treatment In People VImentioning
confidence: 93%
“… 160 Outcomes of these interventions may also depend largely on the age of the individual. While prior studies of psychosocial interventions demonstrate some degree of efficacy in older adults with vision loss, and particularly AMD, 161 meta-analytic findings indicate that improvements are less robust in elderly samples. 160 Related to this finding, risk and protective factors for mental health problems in older adults may be different from those of younger people, 29 and therefore treatment may need to be adapted to fit the individual needs of the consumer.…”
Section: Part Ii: Mental Health Assessment and Treatment In People VImentioning
confidence: 93%
“…Although the cause and effect relationship remains unknown, similar etiopathogenic and neuropathogenic mechanisms were suggested [ 38 ]. As for age-related macular degeneration, it is a potentially distressing medical condition because of the vision loss, financial burden of treatment, and long-term need of intraocular injection [ 39 ]. Although the association between age-related macular degeneration and MDD at the neurological level has not been confirmed, one previous study has indicated a possible physiological connection between the diseases [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…В рамках продольного проспективного когортного исследования в Нидерландах, продолжавшегося 24 мес, исследовалась частота возникновения депрессии и тревоги у пожилых людей с нарушениями зрения, у которых исходно не было этих состояний [18,19]. Группа исследуемых состояла из 540 пожилых пациентов (из них 56 % женщин) в возрасте в среднем 75 лет с нарушением зрения.…”
Section: Modern Multicenter Studies Of Psychological Features Proper unclassified